Preparation and characterization of a novel controlled‐release nano‐delivery system loaded with pyraclostrobin via high‐pressure homogenization. Issue 8 (4th May 2020) - Wang, Anqi; Cui, Jianxia; Wang, Yan; Zhu, Huaxin; Li, Ningjun; Wang, Chunxin; Shen, Yue; Liu, Pengfei; Cui, Bo; Sun, Changjiao; Zhao, Xiang; Wang, Chong; et al.
Abstract: BACKGROUND: The development of efficient and safe green pesticides is a scientific strategy to alleviate current pesticide residues, environmental pollution, and threats to non‐target organisms. Pesticide controlled‐release formulations (CRFs) have attracted wide attention because they can control the rate of release of active ingredients and prolong the effective duration. In particular, nanoscale pesticide sustained‐release systems have excellent biological activity and distribution performance because of their small particle size. Some technical difficulties remain in obtaining nanoscale CRFs. RESULTS: We successfully fabricated pyraclostrobin nanosphere CRF by combining high‐pressure homogenization technology and emulsion–solvent evaporation methods. The pyraclostrobin nanospheres had a uniform spherical shape with a mean particle size of 450 nm and polydispersity index of less than 0.3. The pyraclostrobin loading capacity reached 53.6%, with excellent storage stability. The contact angle of nanospheres on cucumber leaf surfaces demonstrated that it had good wettability. Compared with pyraclostrobin technical and commercial formulations, the nanosphere systems showed a significantly sustained release of pyraclostrobin for longer (up to 250 h). A preliminary bioassay against Penicillium ochrochloron showed that the bioactivity and long‐term efficiency of pyraclostrobin nanospheres were superior to those of the commercial formulation. CONCLUSION: This research introduced a simple, fast, expandable method for preparing pyraclostrobin nanospheres. The results showed that pyraclostrobin nanospheres could prolong the duration of pesticide efficacy and enhance bioactivity. Furthermore, this technology provides a platform for scale‐up production of nano‐scale pesticide CRFs. © 2020 Society of Chemical Industry Abstract : Pyraclostrobin controlled‐release nano‐delivery system synthesized by emulsion–solvent evaporation methods combined with high‐pressure homogenization technology, which showed good controlled‐release performance, foliar spreading performance and biological activity. © 2020 Society of Chemical Industry